Model Strategi Pemasaran Usaha Industri Batik (Studi Pada Belva Batik Tulis Madura di Burneh, Kabupaten Bangkalan) - Fajrin Purnomo; Nurita Andriani (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
The purpose of this research is to provide an overview of the marketing strategy model. The research method used is a qualitative descriptive approach. This type of data uses primary data and secondary data. Methods of data collection using interview and documentation techniques. The data analysis method uses data reduction, data presentation, and drawing conclusions. Belva Batik Tulis Madura during the pandemic implemented a product diversification strategy. The price strategy for the Belva Batik Tulis Madura before and during the COVID-19 pandemic did not change the price strategy. The location strategy at Belva Batik Tulis Madura before the COVID-19 pandemic was carried out through two sales points and distributors, while during the COVID-19 pandemic only opened one sales location and did not use distributors. The promotional strategy before the COVID-19 pandemic used BBM, WhatsApp, Instagram, exhibitions, WOM, billboards, and business cards. Meanwhile, during the COVID-19 pandemic using WhatsApp and Instagram.